If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -7 + y + 47 = 6y + 40 + -4y Reorder the terms: -7 + 47 + 3y + y = 6y + 40 + -4y Combine like terms: -7 + 47 = 40 40 + 3y + y = 6y + 40 + -4y Combine like terms: 3y + y = 4y 40 + 4y = 6y + 40 + -4y Reorder the terms: 40 + 4y = 40 + 6y + -4y Combine like terms: 6y + -4y = 2y 40 + 4y = 40 + 2y Add '-40' to each side of the equation. 40 + -40 + 4y = 40 + -40 + 2y Combine like terms: 40 + -40 = 0 0 + 4y = 40 + -40 + 2y 4y = 40 + -40 + 2y Combine like terms: 40 + -40 = 0 4y = 0 + 2y 4y = 2y Solving 4y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4y + -2y = 2y + -2y Combine like terms: 4y + -2y = 2y 2y = 2y + -2y Combine like terms: 2y + -2y = 0 2y = 0 Divide each side by '2'. y = 0 Simplifying y = 0
| (3x+2)(3x-2)=77 | | -5m-20=-2m-2 | | 4v^2-5v=26 | | 8y+15=7 | | 3x+20=x+2 | | 5x-1/6x-9-5x-10/8x^2-18=9x-4/8x-12 | | 3x+6+9=12 | | -3(4T-1)=-(t-14) | | 9h-27=36 | | 4/5x5/16 | | -5b+7-4b-2-b=-15 | | 4(3+4)-3=25 | | 2x+20=94 | | 5a+9b=360 | | 4/3T=-36 | | 4(3+4x)=25 | | 4c-8=5c+15 | | (x-7)(x+3)=24 | | 10p-7=24 | | -11.4-m=10.9 | | 20p-7=24 | | 37+(9x-1)=90 | | 3x/4-2/3=5/6 | | (3y+7)(-4x+2)= | | (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 |